Use of imiquimod topical therapy for management of malignant melanoma positive margins - Lewis, Katelyn; Islam, Sara; Alper, David P.; Carney, Martin J.; Choi, Jennifer; Leventhal, Jonathan; Ariyan, Stephan; Baumann, Raymond; Olino, Kelly; Clune, James (Frontiers in Oncology, 2025)
IntroductionThe treatment of positive margins following primary resection of cutaneous melanoma remains controversial with the current standard of care being repeat surgical resection. 5% topical imiquimod therapy has been proposed as an alternative treatment for positive in-situ surgical margins. This study revisits the use of 5% topical imiquimod therapy as a method of clearing positive surgical margins following primary excision of cutaneous melanoma.MethodsA retrospective chart review of all Yale Melanoma Registry Database patients with positive melanoma in situ margins after excision of primary melanoma between January 2008 and December 2021 was conducted. Patients were included if they received 5% topical imiquimod therapy for treatment of positive melanoma in situ surgical margins. Demographics, treatment duration, treatment response, complications, follow-up time, and associated costs were recorded.ResultsA total of 69 patients with positive margins post wide local excisions were treated with topical imiquimod therapy. 38 of these patients had histological diagnosis of melanoma at primary excision while the remainder, 31, had MIS. Five patients were excluded due to follow-up with an outside dermatologist, leaving 64 patients in the final cohort. Fifty-two percent of patients were female with a median age of 73 years old in the entire cohort of patients. Treatment duration with imiquimod ranged from four to twelve weeks of therapy with a median duration of 12 weeks. Clinical response rate after final biopsies was 84% over an average follow-up duration of 36 months. Six patients (8.7%) had recurrences in follow-up after negative scouting biopsies following treatment with an average follow-up duration of 1086 days or approximately 36 months.ConclusionThe use of 5% topical imiquimod therapy is a safe, cost-effective, and reasonable alternative approach in the management of positive surgical margins. The degree of inflammation around the site of disease may be used as a reliable predictor of outcome.